Analysis of the influence of switching related parameters in the dab converter under soft-switching - Oggier, German Gustavo (2013)
An analysis of a dual active bridge (DAB) converter under soft-switching mode in the whole operating range is presented in this paper. A detailed study of the impact ofthe transformer magnetizing inductance, LM,and snubber capacitance, Cxx, parameters on the soft-switching regions is carried out to obtain some design considerations. Simulation and experimental results which validate the theoretical analysis are also presented.